LIQUID CREATININE AMNIOTIC - Berrocal Curiel, Jorge (2015)
162 tests were carried creatinine in amniotic fluid in normal pregnant women who attend the Central Military Hospital, Lima, in stages of gestation ranging from 24 to 42 weeks. The amniotic fluid was obtained by abdominal omniocentesis and vaginally. For the assay of creatinine was used Wu Follin method based on Jaffe reaction. Average values have been established in amniotic fluid creatinine in the different groups entered in the respective tables, where it is noted that this substance will progressively increase as the pregnancy progresses. They have performed statistical calculations to present the results of this work.